A Neuromonitoring Approach to Facial Nerve Preservation During Image-guided Robotic Cochlear Implantation. Issue 1 (January 2016) - Ansó, Juan; Dür, Cilgia; Gavaghan, Kate; Rohrbach, Helene; Gerber, Nicolas; Williamson, Tom; Calvo, Enric M.; Balmer, Thomas Wyss; Precht, Christina; Ferrario, Damien; Dettmer, Matthias S.; Rösler, Kai M.; et al.
Abstract : Hypothesis: A multielectrode probe in combination with an optimized stimulation protocol could provide sufficient sensitivity and specificity to act as an effective safety mechanism for preservation of the facial nerve in case of an unsafe drill distance during image-guided cochlear implantation. Background: A minimally invasive cochlear implantation is enabled by image-guided and robotic-assisted drilling of an access tunnel to the middle ear cavity. The approach requires the drill to pass at distances below 1 mm from the facial nerve and thus safety mechanisms for protecting this critical structure are required. Neuromonitoring is currently used to determine facial nerve proximity in mastoidectomy but lacks sensitivity and specificity necessaries to effectively distinguish the close distance ranges experienced in the minimally invasive approach, possibly because of current shunting of uninsulated stimulating drilling tools in the drill tunnel and because of nonoptimized stimulation parameters. To this end, we propose an advanced neuromonitoring approach using varying levels of stimulation parameters together with an integrated bipolar and monopolar stimulating probe. Materials and Methods: An in vivo study (sheep model) was conducted in which measurements at specifically planned and navigated lateral distances from the facial nerve were performed to determine if specific sets of stimulation parameters in combination with the proposed neuromonitoring system could reliably detect an imminent collision with the facial nerve. For the accurate positioning of the neuromonitoring probe, a dedicated robotic system for image-guided cochlear implantation was used and drilling accuracy was corrected on postoperative microcomputed tomographic images. Results: From 29 trajectories analyzed in five different subjects, a correlation between stimulus threshold and drill-to-facial nerve distance was found in trajectories colliding with the facial nerve (distance <0.1 mm). The shortest pulse duration that provided the highest linear correlation between stimulation intensity and drill-to-facial nerve distance was 250 μs. Only at low stimulus intensity values (⩽0.3 mA) and with the bipolar configurations of the probe did the neuromonitoring system enable sufficient lateral specificity (>95%) at distances to the facial nerve below 0.5 mm. However, reduction in stimulus threshold to 0.3 mA or lower resulted in a decrease of facial nerve distance detection range below 0.1 mm (>95% sensitivity). Subsequent histopathology follow-up of three representative cases where the neuromonitoring system could reliably detect a collision with the facial nerve (distance <0.1 mm) revealed either mild or inexistent damage to the nerve fascicles. Conclusion: Our findings suggest that although no general correlation between facial nerve distance and stimulation threshold existed, possibly because of variances in patient-specific anatomy, correlations at very close distances to the facial nerve and high levels of specificity would enable a binary response warning system to be developed using the proposed probe at low stimulation currents.